Identification of Pre- and Post-Treatment Markers, Clinical, and Laboratory Parameters Associated with Outcome in Renal Cancer Patients Treated with MVA-5T4 - Amato, Robert; Said, Rabih (Frontiers in Oncology, 2013)
The recent approvals of immunotherapeutic agents (Sipuleucel-T and Ipilimumab) for the treatment of different solid tumors gave a boost to the growing cancer immunotherapy field, even though few immunotherapy studies have demonstrated convincingly that there is a direct link between the predicted mode of action of an immunological compound and therapeutic benefit. MVA-5T4 (TroVax®) is a novel vaccine combining the tumor-associated antigen 5T4 to an engineered vector-modified vaccinia Ankara (MVA). MVA helps to express the oncofetal 5T4 antigen and subsequently trigger a tumor-directed immune reaction. The safety and clinical benefit reported in multiple phase I and II clinical trials using MVA-5T4 were encouraging; immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in most of the nine phase II trials. In particular, clinical studies conducted in renal cell carcinoma (RCC) patients have demonstrated an association between 5T4-specific (but not MVA) antibody responses and enhanced survival. This review describes the clinical studies using MVA-5T4 conducted in RCC that convincingly demonstrated that an antigen-specific immune response induced by vaccination is associated with enhanced patient survival and is not simply a function of the general “health” of patients. We will also provide our expert opinions on possible future better-designed clinical trials based on relevant biomarkers. In addition, various combinations of MVA-5T4 and different and newer immunomodulator agents with promising clinical benefit will be discussed.